Art Matters : Hemingway, Craft, and the Creation of the Modern Short Story - Lamb, Robert Paul, 1951- (Book collections on Project MUSE., 2010)
In Art Matters, Robert Paul Lamb provides the definitive study of Ernest Hemingway's short story aesthetics. Lamb locates Hemingway's art in literary historical contexts and explains what he learned from earlier artists, including Edgar Allan Poe, Paul Cezanne, Henry James, Guy de Maupassant, Anton Chekhov, Stephen Crane, Gertrude Stein, James Joyce, and Ezra Pound. Examining how Hemingway developed this inheritance, Lamb insightfully charts the evolution of the unique style and innovative techniques that would forever change the nature of short fiction.Art Matters opens with an analysis of th.